PENINGKATAN PRODUKTIVITAS MELALUI PENGURANGAN DEFECT PRODUK KABEL FIBER OPTIK DENGAN METODE TPM FOCUS IMPROVEMENT SEBAGAI KONTRIBUSI SDGS - Sulistyo, Arif Budi; Solihati, Tifani Intan; Hidayanti, Nur; Siagian, William Harapan Restadamai (Teknik Industri Unikom, 2023)
PT. XYZ is a manufacturer of fiber optic cables in Indonesia. This company is known as a premium manufacturer with high-quality products and has expertise in producing various variants of fiber optic cables. Currently, optical cable is a vital material supporting infrastructure development in Indonesia, especially in the field of telecommunications networks, which contributes to Indonesia's SDGs (Sustainable Development Goals) in the social pillars (quality education) and economic pillars (industry, innovation, and infrastructure). There is a problem, namely a decrease in the productivity of machine performance due to an increase in product defects, which is around 9% which can disrupt supply in the market. Many defects occur in Jacketing machines. The purpose of this study is to overcome problems with jacketing machines, so that machine productivity increases and the number of defects decreases